Irrigataion and Economic Development (A Comparative Regional Analysis of Karnataka State) - Madari, D. M; Deene, Shiv Kumar (Journal of Commerce and Trade, 2009)
The economic development of Karnataka is mainly dependent on the development of agriculture. Irrigation is the main infrastructure for development of this vital sector. The modernization of agricultural practices vis-à-vis increase in productivity of crops cannot be conceived in absence of assured irrigation facilities. The importance of irrigation development in a State like Karnataka therefore, needs no special emphasis. Like other leading States in India, the programmes for development of irrigation in Karnataka has been launched under two heads, viz., Major, Minor& Medium Irrigation . The present paper attempts to identify the irrigation and agricultural development disparities in the state, regions which beset within the purview of other regions of the state and provide justification for renewed and reinforced as well as developmental focus on this region.